On investigation of capillary and pressure involved working constrains for water-driven and sintered-powder heat pipes using a semi-empirical model - Yu-Ren Lin; Tsrong-Yi Wen (Case Studies in Thermal Engineering)
Heat pipes are efficient heat spreaders commonly used for thermal management in various energy and electronic systems. A heat pipe works based on phase change processes and capillary/pressure-driven circulation of working fluid. However, dryout can occur when the circulation collapses (e.g., liquid flows against gravity or excessive heat input), leading to failure. This paper proposes a semi-empirical model for water-driven and sintered-powder heat pipes to address the correlations among acceleration (gravity), length, heat input, wick porosity, wick thickness, and vapor core diameter. Additionally, this paper uses analysis of variance (ANOVA) to analyze the influence of these parameters of interest on the maximum acceleration load and critical heat input a heat pipe can handle. The proposed model is verified by comparing with experimental data from the literature, and the results show good agreement. To maximize the possible working acceleration field, the ANOVA suggests that a heat pipe should be short and wide (large diameter), operate with a low heat input, and use a thick wick with low porosity. On the other hand, to boost the critical heat input, the ANOVA suggests that a heat pipe should be short and wide (large diameter), and use a thick wick with high porosity.